0651 Estimating Burden of Disease Among Blind Individuals With Non 24 Hour Sleep Wake Disorder. (27th April 2018) - Van Draanen, L; Xiao, C; Polymeropoulos, M
Abstract: Introduction: Non 24 Hour Sleep Wake Disorder (N24HSWD) is a circadian rhythm disorder with a significant impact on social and occupational functioning. We utilized longitudinal sleep diary data in order to quantify the burden of disease in blind patients with N24HSWD. Daytime sleep episodes interfere with school work and social activities and therefore Daytime Sleep Free Days (DSFD) can act as a surrogate of healthy days for patients with N24HSWD. Methods: Daytime sleep diary data were collected and analyzed in a cohort of 178 blind individuals presenting with a sleep complaint, 121 of which had N24HSWD and 57 did not. Data collection extended to approximately 90 days and DSFD was calculated in 30 day units. Sleep duration was analyzed using an ANCOVA model and DSFD analysis was performed by a non-parametric test. Results: N24HSWD patients had more frequent and longer episodes of daytime sleep as compared to a control group. N24HSWD patients had a duration of daytime sleep of 36 minutes per day, and control patients daytime sleep duration was 23 minutes per day (pvalue = 0.0006). In a categorical analysis N24HSWD patients slept 2 hours or more for 12 out of 30 days, compared with 7 out of 30 days for the control group (pvalue < 0.0001). N24HSWD patients also had significantly fewer healthy days, defined by daytime sleep free days (DSFD), as compared to the control group, 11 versus 17 respectively in a 30 day period (pvalue < 0.0001). Conclusion: Daytime sleep free days (DSFD) is a useful and specific measure of disease burden in patients with N24HSWD and it is predicted to be correlated with the standardized HRQOL-4, Healthy Days measurement. Support (If Any): This work was supported by Vanda Pharmaceuticals Inc.